Information System Governance Evaluation at Diskominfo Central Java Using COBIT 2019 Framework - Zaini, Ahmad; Widodo, Aris Puji; Nugraheni, Dinar Mutiara Kusumo (Universitas Negeri Semarang, 2025)
Purpose: To evaluate the governance of the LaporGub Central Java service portal information system using the COBIT 2019 framework to obtain a comprehensive overview of the implemented capability levels. Methods: This study employs a qualitative method using the COBIT 2019 framework to assess capability levels, which is further combined with CMMI to provide improvement recommendations. The method produces valid and accurate results as respondents are selected using the RACI model, and the assessment is conducted at the subdomain level. Consequently, each domain yields valid outcomes, enabling precise and well-targeted recommendations. Results: This study successfully determined the level of LaporGub service capability using COBIT 2019 and showed that most domains have achieved, and in some cases even exceeded, the set targets. However, several areas still require improvement, especially in services security and business process control, as well as problem management. These findings indicate that the Central Java Provincial Communication and Information Office has a strong foundation in operational management and service sustainability. With proper improvements in IT governance, LaporGub is expected to serve as a model for adaptive and accountable digital public services that can be replicated in other regions across Indonesia. Novelty: This study introduces innovation by integrating COBIT 2019 with CMMI, an uncommon combination in capability level assessments within government institutions. Innovative techniques such as text development, respondent questionnaires based on the RACI model, and interviews are used to avoid redundancy in the research findings. By utilizing questionnaires, interviews, and document reviews, this approach enhances the validity of the study results.